Scientific thesaurus of educational publications as a structural element of content in the management of educational process - Kharkivska, A. A. (Problems of Engineer-Pedagogical Education, 2018)
The article analyzes the problems of selecting and structuring of educational materials and it also shows the feasibility of using scientific thesaurus as a structural element of information resource management in the educational process when we classify educational publications. The work characterizes types of educational and methodic publications and it gives their classification. The paper presents a concise methodology for writing textbooks, educational, educational and methodic, methodic textbooks, readers, didactic materials, references etc. Using modern scientific thesaurus the author offers the system of educational works that can be divided into 4 groups: software-methodic, educational, supporting and educational and methodic works. The article proves that scientific and pedagogical workers can use thesaurus in classifying writing and structuring educational methodic, scientific and pedagogical workers as well as their competence level and the elevation of the quality in the management of educational process.